Activation likelihood estimation identifies brain regions activated during puncturing at Hegu in healthy volunteers: A meta-analysis - Gao, Zhen; Cui, Mengjie; Zhang, Jing; Ji, Laixi (Frontiers in Neuroscience, 2022)
Background: Hegu is the most commonly used acupoints for pain relief. Recently, several functional neuroimaging studies have been performed on acupuncture at Hegu in healthy volunteers, but these studies have yielded diverse findings. Therefore, there is an urgent need to understand the brain response characteristics of acupuncture at Hegu. Methods: Neuroimaging studies on acupuncture at Hegu published before October 2022 were collected from PubMed, Web of Science, Google Scholar, Embase, and CNKI (China National Knowledge Infrastructure) databases, and were screened by strict inclusion and exclusion criteria. The extraction of brain coordinates was performed by two independent researchers, and the results were analyzed using activation likelihood estimation (ALE) analysis based on quantitative coordinates. Results: In total, 338 studies were searched, of which 19 studies were included in the final analysis after a rigorous double-blind screening review. Activation likelihood estimation showed that postcentral gyrus, inferior parietal lobule, claustrum, insula, thalamus, and superior temporal gyrus in the left brain were activated, whereas the anterior cingulate, caudate, superior temporal gyrus, parahippocampal gyrus, middle temporal gyrus, and uncus in the left brain and the anterior cingulate, medial frontal gyrus in the right brain were deactivated. Conclusions: Acupuncture at Hegu in healthy volunteers did not reveal specific brain regions. This finding implies that organismal status of the study subjects may have an important impact on the effect of acupoints.